Contextual factors affecting the implementation of an anemia focused virtual counseling intervention for pregnant women in plains Nepal: a mixed methods process evaluation - Sanju Bhattarai; Samata Kumari Yadav; Bibhu Thapaliya; Santosh Giri; Basudev Bhattarai; Suprich Sapkota; Shraddha Manandhar; Abriti Arjyal; Naomi Saville; Helen Harris-Fry; Hassan Haghparast-Bidgoli; Andrew Copas; et al. (BMC, 2023)
Abstract Background Anemia is estimated to cause 115,000 maternal deaths each year. In Nepal, 46% of pregnant women have anemia. As part of an integrated anemia-prevention strategy, family engagement and counseling of pregnant women can increase compliance to iron folic acid tablets, but marginalized women often have lower access to these interventions. We implemented the VALID (Virtual antenatal intervention for improved diet and iron intake) randomized controlled trial to test a family-focused virtual counseling mHealth intervention designed to inclusively increase iron folic acid compliance in rural Nepal; here we report findings from our process evaluation research. Methods We conducted semi structured interviews with 20 pregnant women who had received the intervention, eight husbands, seven mothers-in-laws and four health workers. We did four focus groups discussions with intervention implementers, 39 observations of counseling, and used routine monitoring data in our evaluation. We used inductive and deductive analysis of qualitative data, and descriptive statistics of monitoring data. Results We were able to implement the intervention largely as planned and all participants liked the dialogical counseling approach and use of story-telling to trigger conversation. However, an unreliable and inaccessible mobile network impeded training families about how to use the mobile device, arrange the counseling time, and conduct the counseling. Women were not equally confident using mobile devices, and the need to frequently visit households to troubleshoot negated the virtual nature of the intervention for some. Women's lack of agency restricted both their ability to speak freely and their mobility, which meant that some women were unable to move to areas with better mobile reception. It was difficult for some women to schedule the counseling, as there were competing demands on their time. Family members were difficult to engage because they were often working outside the home; the small screen made it difficult to interact, and some women were uncomfortable speaking in front of family members. Conclusions It is important to understand gender norms, mobile access, and mobile literacy before implementing an mHealth intervention. The contextual barriers to implementation meant that we were not able to engage family members as much as we had hoped, and we were not able to minimize in-person contact with families. We recommend a flexible approach to mHealth interventions which can be responsive to local context and the situation of participants. Home visits may be more effective for those women who are most marginalized, lack confidence in using a mobile device, and where internet access is poor.